Incidence of cardiovascular events in patients with chronic myeloid leukaemia treated with tyrosine kinase inhibitors. Issue 2 (7th February 2022) - Casavecchia, Grazia; Spinosa, Giuseppina; De Gennaro, Luisa; Zicchino, Stefano; Gravina, Matteo; Magnesa, Michele; Di Biase, Matteo; Brunetti, Natale Daniele
Abstract: Background: The introduction of imatinib and tyrosine kinase inhibitors as therapeutic strategy for Philadelphia chromosome-positive chronic myeloid leukaemia (CML) has represented an important step forward for treatment of this disease. The aim of this study was therefore to evaluate the incidence of cardiovascular adverse events (CVEs) in patients affected by CML treated with TKI in an observational prospective study. Methods: All consecutive patients affected by CML and treated with TKI in our Institution were enrolled in the study from February 2005 to September 2018 with a clinical, laboratory and instrumental follow-up. Results: Sixty-one consecutive patients were enrolled, 29 with imatinib, 15 with nilotinib, 11 with dasatinib, 3 with bosutinib and 3 with ponatinib. Neither patients in therapy with bosutinib nor with nilotinib had CVE during follow-up. Incidence rates per person/year were 0 for bosutinib and nilotinib, 0.15 for dasatinib, 0.19 for imatinib and 1.69 for ponatinib (Log Rank p  < 0.05); differences in terms of incidence of adverse outcomes remained significant also after multivariate correction. Conclusions: In patients with CML treated with TKIs, therapy with ponatinib was associated with a higher risk of CVE than other TKIs. The lowest incidence of CVE was associated with bosutinib and nilotinib.